Kidnapping In Nigeria, The Impact On Girl-Child Education - Onyido, Josephine Azuka (Archives of Business Research, 2019)
Kidnapping is a serious injustice to the human race as a result of its impact on the society. Once seen as a foreign problem, kidnapping today has spread across every part of the country threatening its national peace and development. In recent times, there has been an upsurge in the abduction of the girl-child and the recent abduction of school girls in Dapchi in Yobe state clearly comes to mind. This paper therefore seeks to critically analyze the impact kidnapping has on the education of the girl-child in Nigeria. It highlights the importance of the girl-child in national development and establishes that kidnapping can be as a result of agitation, financial or terroristic intent and the resultant impact it has on the emotional state of the girl-child while concluding that Nigerians educational system has seriously been impacted by kidnapping activities particularly in the northern parts of Nigeria. It recommends a number of solutions which include that; stiffer penalties should be imposed on kidnappers, the government should adopt poverty alleviation and empowerment programmes aimed at creating avenues for entrepreneurship, non-governmental bodies in partnership with the government should organize sensitization programmes aimed at discouraging kidnapping and highlighting the impact kidnapping has on victims, Security agencies should be adequately funded and equipped to continue the fight to rid Nigeria of terrorist elements, legislations that aim to empower and encourage gender equity in the Nigerian society should be introduced to encourage the enrolment of the girl-child in schools.